Pentaploid Wheat Hybrids: Applications, Characterisation, and Challenges - Padmanaban, Sriram; Zhang, Peng; Hare, Ray A.; Sutherland, Mark W.; Martin, Anke (Frontiers in Plant Science, 2017)
Abstract Interspecific hybridisation between hexaploid and tetraploid wheat species leads to the development of F1 pentaploid hybrids with unique chromosomal constitutions. Pentaploid hybrids derived from bread wheat (Triticum aestivum L.) and durum wheat (T. turgidum spp. Durum Desf.) crosses can improve the genetic background of either parent by transferring traits of interest. The genetic variability derived from bread and durum wheat and transferred into pentaploid hybrids has the potential to improve disease resistance, abiotic tolerance, and grain quality, and to enhance agronomic characters. Nonetheless, pentaploid wheat hybrids have not been fully exploited in breeding programs aimed at improving crops. There are several potential barriers for efficient pentaploid wheat production, such as low pollen compatibility, poor seed set, failed seedling establishment, and frequent sterility in F1 hybrids. However, most of the barriers can be overcome by selecting the parental genotype while crossing and using the higher ploidy level parent as the maternal parent. In this review, we summarise the current research on pentaploid wheat hybrids and analyse the advantages and pitfalls of current methods used to assess pentaploid-derived lines. Furthermore, we discuss current and potential applications in commercial breeding programs and future directions of research into pentaploid wheat.